The Wharton index of capacity utilization - Klein, Lawrence R.; Summers, Robert; University of Pennsylvania (Philadelphia : Economics Research Unit, Dept. of Economics, Wharton School of Finance and Commerce, University of Pennsylvania, 1966)
The book examines economic activity as it relates to capacity utilization and attempt to develop a variable econometric models that help to understand economic movement.
Bibliography: p. 93-94.
usc 14/02/2019
Loans
Keywords: Industries; Industrial capacity; United States